Effectiveness and Side Effects of Natural and Modern Contraceptives in Multiparous Indonesian Families: Systematic Review - Shalvira Purnama; Saufa Ayudia Pratiwi; Vincent Christopher Pakendek; Tsabitha Ramadhani; Muhammad Awaludin Rachman; Arroyyani Shofiatun Nisa'; Arifin Ilham Syafa'at; Theodorus Sebastian De Rozari; Maryam Shabrina; Syarifah Saniinah Yasmine; Khairunnida Rahma (Mulawarman International Conference on Tropical Public Health, 2025)
Family planning enables couples to regulate childbirth and improve reproductive health. This systematic literature review compares the effectiveness and side effects of natural and modern contraceptive methods among multiparous families in Indonesia. The review followed the PRISMA guidelines. Literature searches were conducted through ScienceDirect, PubMed, and Google Scholar using the keywords "natural contraception," "modern contraception," "multiparity," "effectiveness," and "side effects." Nineteen articles published between 2015 and 2025 were analyzed. Findings indicate that modern contraceptive methods such as intrauterine devices (IUDs), implants, injections, pills, and surgical procedures (MOW and MOP) have higher effectiveness rates (98–99%) compared to natural methods including the calendar, cervical mucus, and withdrawal techniques (70– 95%). However, modern methods are often associated with minor side effects, such as menstrual irregularities, weight changes, and mood fluctuations, while serious complications are rare. Natural methods are generally free from physical side effects but carry a higher failure rate if not practiced consistently. Social, cultural, and economic factors strongly influence contraceptive choice among multiparous families. Although modern contraception is more effective, stigma, misinformation, and limited accessibility continue to hinder optimal utilization. Further large-scale analytical studies are required to assess long-term safety and to identify contextual factors that influence contraceptive decision-making in Indonesia.